I frutti dello Spirito Santo - il commento di san Tommaso d’Aquino ai Gal 5,22ss - Dąbrowski, Wiesław (Poznańskie Studia Teologiczne, 2015)
In the presentation of the subject – preceded by an Introduction, where the Aquinas is presented as Bible’s Commentator – the author examines the saint Thomas’ interpretations of saint Paul’s texts regarding the theme of this research, confronted with the contemporary exegesis, and presents three points: 1 – The vices (Gal 5,19-21); 2 – The fruits of the Holy Spirit (Gal 5,22-23a); 3 – Against such there is no Law (Gal 5,23b; whit the interpretation of Gal 5,24-25). All this permits to the author to conclude that the doctrine of the fruits of the Holy Spirit presented by Saint Thomas in this Commentary is very clear, rich and remains valid and topical and permits to remain in the faith, morality and spirituality of the Church.